The stigma against tuberculosis in students of the faculty of medicine of a public university, 2017 - Reyes Puma, Nora (2018)
Introduction. Tuberculosis is a public health problem in our country. Affected patients are slow to access health services, among other factors due to the stigma and social discrimination that this disease has in the population. In addition, stigma has an impact on the social and family relationship of affected patients. The objective of the present study was to quantify the stigma in students of the faculty of medicine of a public university. Methods. An observational, descriptive and transversal study was carried out. A previously validated questionnaire was applied to students of the first three years of medical school, in order to quantify the stigma of tuberculosis. Results. The questionnaire was applied to 505 students of the medical school. 39% of the student population showed a moderate and great stigma in front of the people affected by tuberculosis; likewise, 38% showed a slight stigma and 23% did not present stigma against this disease. Conclusions. There is moderate and great stigma in 39% of the students of the medical school studied.